Features of seismicity triggered by ripple-fired explosions at the Korobkovskoye iron ore deposit - Ostapchuk Aleksey; Morozova Kseniya; Besedina Alina; Gridin Grigorii; Grygoryeva Antonina; Pavlov Dmitry (Russian Journal of Earth Sciences)
Intensification of mining activities often lead to nucleation of strong earthquakes and fault-slip bursts in areas that were previously thought to be aseismic or of low seismicity. Triggering strong seismic events associates with slips on existing tectonic faults and large fractures, whose structures essentially alter along strike. This work analyzes parameters of mine seismicity at the Korobkovskoye iron ore deposit, within which the large North-Eastern fault is localized. The goal of this analysis is to assess the probability of triggering strong seismic events at the fault segments with different structures of the core. The technique of ripple-fired blasting and horizon mining are employed in developing the deposit. This provokes weak seismic activity within the mine field. When explosions are hold in host rock, seismic events localize within the blasted chamber. The magnitude statistics displays distribution that obeys a power law, and the scaling exponent 𝑏-value, as a rule, is less than 2. When explosions are hold in the vicinity of the fault, seismic events localize along its trace, and the 𝑏-value, as a rule, exceeds 2. The main feature of seismicity at the Korobkovskoye iron ore deposit is that the induced events are of low radiative efficiency of 8,9 × 10−9–4,9 × 10−7 J/(N·m), which corresponds to “slow earthquakes”. The core of the North-Eastern fault contains mainly velocity-strengthening rocks, causing initiation of slow slip events. It is this circumstance that probably determines initiation of slow events. Linking the data of seismic monitoring and the structural and rheological properties of materials that compose the fault core allows to suggest that within the mine field in the vicinity of the North-Eastern fault the accumulated deformations can release mainly via slow and aseismic slips.